Marriage of a Widowed Woman from Syafiq Riza Basalamah's Perspective - Salma,; Nurul Fahmi, Muhammad (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
The status of a widowed woman is a difficult and emotional challenge because they must take care of their needs and their children alone, and they also have to feel the psychological burden of the surrounding community, because society in general still views widow status negatively. Widowed women, if they decide to remarry after a divorce, are underestimated by most people and even labeled with negative things. This research was conducted with the author raising the perspective of an Ahlusunnah da'i, namely Syafiq Riza bin Hasan bin Abdul Qadir bin Salim Basalamah. He is an Ahlusunnah da'i who often discusses Islamic law and marriage based on the foundation of the Qur'an and Hadith. Hence, the purpose of this study is to provide insight and information about the law of remarriage for widowed women and the wisdom of marrying widowed women from an Islamic perspective and the perspective of Syafiq Riza Basalamah. This research was conducted using a qualitative approach method that uses content analysis where data sources are obtained from YouTube videos, books, and several scientific papers. Thus, the results of this study have found that the law of remarriage for widowed women from an Islamic perspective and the perspective of Syafiq Riza Basalamah is that it is permissible not to do so and is obligatory under certain conditions, and helping widows is not only marrying but also meeting their needs.